Ser idoso, sexualidade e cuidados preventivos no atual cenário da maior longevidade e envelhecimento populacional.: estudo de caso no município de Natal/RN - Cristiane Alessandra Domingos de Araújo (2018)
The bigger longevity caused the desire for better living conditions among the elderly, which allowed them to keep active and with the minimum of commitment in their daily lives. Living better, healthier, more autonomous and independent, activities which were formerly exercised until adulthood are now extended beyond the old ages. The time spent on household activities and the raising of children and grandchildren has been reduced and, on the other hand, investment in leisure, well-being and quality of life has increased. In this way, sexuality, inherent in all living species, is also sought after in old age. However, due to cultural and personal factors, many older people are exposed to Sexually Transmitted Infections (STIs) and sexual practices, which should increase well-being, may cause deterioration of the additional years gained by longevity increasing. In this context, this thesis aimed to analyze the perception of sexuality among people from the age of 60, discussing aspects such as the identity of "Being old" and preventive care to STI's, identifying differences between men and women. With regard to preventive care two most usual risk behaviors have been investigated: the multiplicity of partnerships and the lack of condom use in sexual relations. To reach the goal, a qualitative approach has been used, through two techniques: focus group with elderly women and semi-structured interview with elderly men. The technique of selection of individuals was snowball or indication. The target group consisted of elderly people, both genders, aged 60 and over, living in the brazilian municipality of Natal / RN. The analyzing method was the Attride-Stirling proposal. Among the results, on the one hand, there is a greater female empowerment, resulting, among others, in financial stability. This encourages the elderly to rationalize the losses and gains of possible romantic / love involvement. On the other hand, the elderly man called attention by the systematic disuse of condoms in sexual relationships, in which they are associated, basically, with extramarital relationships and problems in the genitourinary system. From there, it can be deduced that the Sexual Health policies directed to the elderly population should be based on people close to them, for example, Family Health Strategy teams and 'belonging social groups'. It is suggested that HIV / AIDS prevention campaigns must be unjoined from the path of sexual contagion. After all, the elderly associate it with the current marital status, therefore, to a probable unfaithfullment of the partner, if it has. In addition, it is essential to encourage, in this segment, anti-HIV testing by including it in routine exams.